Growth , yield and quality of medicinal plant Chia (Salvia hispanica) as influenced by planting methods and density - KUNDU, C K; ANAND, N R; BANERJEE, H; DEVI, N M; GUNRI, S K; NAYAK, L; MONDAL, G; DE, S K (The Indian Journal of Agricultural Sciences, 2023)
An experiment was conducted at Central Research Farm, Gayeshpur, Nadia under BCKV, West Bengal to assess the impact of plant density and planting methods on growth, yield and quality attributes of chia (Salvia hispanica L.) grown during winter (rabi) seasons of 2019–20 and 2020–21. Treatments were distributed in split-plot design, with 2 establishment methods (M1, direct sowing and M2, Transplanting) in main plots and 4 planting density (S1, 60 cm × 50 cm = 33,333 plants/ha; S2, 50 cm × 50 cm = 40,000 plants/ha; S3, 50 cm × 25 cm = 80,000 plants/ha; S4, 50 cm × 20 cm = 1,00,000 plants/ha) in sub-plots. Crop under direct sowing with closer spacing (50 cm × 20 cm) had the greater number of primary branch (15.7/plant), primary branch length (38.4 cm) and main inflorescence length (25.9 cm), thereby reflecting superiority of this treatment combination over others. The same treatment combination produced significantly the highest grain (671.7 kg/ha), stem (1109.4 kg/ha) and husk yield (375.2 kg/ha), which led to increase harvest index (31.2). The greatest economic response in terms of gross return (228.4 × 103 ₹/ha), net return (166.3 × 103 ₹/ha) and B: C ratio (3.67) was recorded in crop under the same treatment combination. Based on quadratic regression equation, the optimum plant density of chia was calculated as 71,428 plants/ha. Thus, direct seed sowing at a density of 71,428 plants/ha (spacing ~ 55 cm × 25 cm) can be done for chia cultivation during rabi season in West Bengal condition.